Peningkatan Literasi Digital Remaja dalam Menyikapi Pengaruh Media Sosial terhadap Gaya Hidup di Era Digital - Matius Adwil Kaha; Sumiati Rewa Rara; Ndara Takka; Sitti Aisah M.Ahmad; Noksia Bora; Pelipus Maghu Ate; Petrus Dima Rato; Siprianus Andreanto Horo; Meldianus Bili; Solviana Sogara; Nelson Ngila Wogara; Risda Ranbu Awa; Indriani Tamo Inya; Roslia Ngongo (Repeater : Publikasi Teknik Informatika dan Jaringan, 2026)
The rapid development of information and communication technology has increased the use of social media among adolescents as a means of communication, obtaining information, entertainment, and self-expression. However, the use of social media without adequate digital literacy skills can lead to negative impacts, such as the spread of misinformation, consumerist behavior, social media addiction, and declining quality of social interactions. This community service activity aims to improve adolescents' digital literacy in responding to the influence of social media on their lifestyles in the digital era. The methods employed include socialization, educational sessions, interactive discussions, and mentoring focused on understanding digital literacy, evaluating information, and utilizing social media in a healthy and productive manner. The results indicate an improvement in participants' understanding of the importance of digital literacy, their ability to identify valid information, recognize the risks of misinformation, and adopt a more critical attitude toward social media content. Participants also demonstrated greater awareness of using social media positively for self-development, creativity, and enhancing useful life skills sustainably